Pemberdayaan Program Urban Farming Untuk Meningkatkan Ketahanan Pangan Dan Kualitas Lingkungan di Kelurahan Gebang Putih Kota Surabaya - Tiara Himma Fadhilah; Adilah Dwita Cahyana; Ferdiansyah Dwiky Nugraha; Gideon Setyo Budiwitjaksono4 (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2024)
The city of Surabaya, as the most populous city in East Java, faces challenges in providing green land and open space for its residents. Thus, urban farming emerged as an innovative solution to overcome limited land in urban areas. This community service aims to empower the residents of Gebang Putih Subdistrict, Surabaya, through an urban farming program. This activity includes outreach and training on urban farming techniques, including hydroponics and growing plants in pots. The results of this activity show that residents gave a positive response and high enthusiasm for this program. Urban farming not only increases food security and family independence but also contributes to improving environmental quality and public health.